Edge of chaos Why democracy is failing to deliver economic growth -- and how to fix it - Moyo, Dambisa (New York Hachette Audio, 2018)
From an internationally acclaimed economist, a provocative call to jump-start economic growth by aggressively overhauling liberal democracy
Keywords: Democracy